Generation and Characterization of iPS Cells Derived from APECED Patients for Gene Correction - Karvonen, Eira; Krohn, Kai J. E.; Ranki, Annamari; Hau, Annika (Frontiers in Endocrinology, 2022)
APECED (Autoimmune-Polyendocrinopathy-Candidiasis-Ectodermal-Dystrophy) is a severe and incurable multiorgan autoimmune disease caused by mutations in the AIRE (autoimmune regulator) gene. Without functional AIRE, the development of central and peripheral immune tolerance is severely impaired allowing the accumulation of autoreactive immune cells in the periphery. This leads to multiple endocrine and non-endocrine autoimmune disorders and mucocutaneous candidiasis in APECED patients. Recent studies have suggested that AIRE also has novel functions in stem cells and contributes to the regulatory network of pluripotency. In preparation of therapeutic gene correction, we generated and assessed patient blood cell-derived iPSCs, potentially suitable for cell therapy in APECED. Here, we describe APECED-patient derived iPSCs’s properties, expression of AIRE as well as classical stem cell markers by qPCR and immunocytochemistry. We further generated self-aggregated EBs of the iPSCs. We show that APECED patient-derived iPSCs and EBs do not have any major proliferative or apoptotic defects and that they express all the classical pluripotency markers similarly to healthy person iPSCs. The results suggest that the common AIRE R257X truncation mutation does not affect stem cell properties and that APECED iPSCs can be propagated in vitro and used for subsequent gene-correction. This first study on APECED patient-derived iPSCs validates their pluripotency and confirms their ability for differentiation and potential therapeutic use.